Microscopic Mass Spectrometry Imaging Reveals the Distribution of Phytochemicals in the Dried Root of Isatis tinctoria - Nie, Li-Xing; Dong, Jing; Huang, Lie-Yan; Qian, Xiu-Yu; Lian, Chao-Jie; Kang, Shuai; Dai, Zhong; Ma, Shuang-Cheng (Frontiers in Pharmacology, 2021)
The dried root of Isatis indigotica is one of the most popular traditional Chinese medicines with well-recognized prevention and treatment effects against viral infections. Above 300 components have been isolated from this herb, but their spatial distributions in the root tissue remain unknown. In recent years, mass spectrometry imaging (MSI) has become a booming technology for capturing the spatial accumulation and localization of molecules in fresh plants, animal or human tissues. However, few studies were conducted on the dried herbal materials due to the obstacles in cryosectioning. In this study, distributions of phytochemicals in the dried root of Isatis indigotica were revealed by microscopic mass spectrometry imaging, with application of atmospheric pressure matrix assisted laser desorption/ionization (AP-MALDI) and ion trap-time-of-flight mass spectrometry (IT-TOF/MS). After optimization of the slice preparation and matrix application, 118 ions were identified without extraction and isolation. And the locations of some metabolites in the dried root of Isatis indigotica were comprehensively visualized for the first time. Combing with partial least squares (PLS) regression, samples collected from four habitats were differentiated unambiguously based on their mass spectrometry imaging.